ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI PISANG DI KECAMATAN PADANG CERMIN KABUPATEN PESAWARAN - Canita, Putri Lepia; Haryono, Dwi; Kasymir, Eka (Lampung University, 2017)
This research aimed to analyze: the amount of household income, the distribution of household income, the level of hosehold welfare of banana farmers. The study is conducted in the subdistrict Padang Cermin, Pesawaran Regency with the consideration that Padang Cermin subdistricti is the center of banana farming. Respondents were 44 farmers who were selected propotionately and randomly. Aanalysis used are descriptive and quantitative analysis. The results showed that average household income of banana farmers in Padang Cermin of Pesawaran Regency was Rp31,423,829.36 per year. It came from banana farming (on farm) amounting to 27.300.193,18 (86.88 persen) and from outside the farm (non-farm) amounting to Rp4.123.636,18 (13.47 persen). The household income of banana farmers in Padang Cermin District was distributed evenly. This was indicated by the value of the Gini Ratio of 0.01. It means that the distribution of household income inequality is still low. Banana farmers in Padang Cermin district were included into barely poor category, amounted to 15.91 percent, fairly 72.73 percent, and decent living 11.36 percent. There were no poorest of the poor, very poor, and the poor. Based on the criteria of the Central Statistics Agency in 2014 households, 90.90 percent banana farmers in Padang Cermin district are in not-prosperous category and 9.10 percent as prosperous farmers. Key words: banana, household welfare, income, income distribution